Early Diagnosis Of Inflammatory Arthritis By Primary Care Physicians Following Training By A Rheumatologist - Magliah R (Dove Medical Press, 2019)
Rami Magliah,1 Waleed Hafiz,2,3 Ziad Abdulaziz Alahmadi,2 Muhammad Irfanullah Siddiqui,4 Haytham Mohamed Ahmed,5 Suzan Mansour Attar,6 Nahed Janoudi,7 Hani Almoallim2,3,7 1Department of Medicine, King Abdullah Medical City, Makkah, Saudi Arabia; 2Department of Medicine, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 3Alzaidi Chair of Research in Rheumatic Diseases, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 4Department of Community Medicine, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 5Pfizer Biopharmaceutical Group, Emerging Markets, Jeddah, Saudi Arabia; 6Department of Medicine, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 7Department of Medicine, Dr. Soliman Fakeeh Hospital, Jeddah, Saudi ArabiaCorrespondence: Waleed HafizDepartment of Medicine, Faculty of Medicine, Umm Al-Qura University, 2254 Al-Taif Road, Al-Mashaer District, Makkah 7250-24255, Saudi ArabiaTel +966 12 527 0000 4041Email waleed_hafiz@hotmail.comBackground: Early diagnosis and therapeutic management of inflammatory arthritis (IA) is crucial for minimizing disease progression and improving outcomes. We recently developed the New Early Arthritis Referral Criteria to help improve the detection of suspected early IA via musculoskeletal (MSK) examination. The present study aimed to evaluate the agreement between rheumatologists and primary care physicians (PCPs) trained by rheumatologists in detecting IA when applying the standardized MSK examination techniques used to develop this criteria in a real-world setting in Jeddah, Saudi Arabia.Methods: This quasi-experimental study was conducted in 4 primary health centers and involved 30 PCPs and 3 rheumatologists. All PCPs were trained by rheumatologists to apply the standardized MSK examination techniques used to develop the New Early Arthritis Referral Criteria. Patients were eligible if they were >18 years of age and presented with small-joint pain that persisted for >6 weeks. Patients were excluded if they had prior diagnosis of osteoarthritis, hand fractures, or rheumatic disease associated with IA. All patients were examined separately by a PCP and a rheumatologist, with the findings compared via kappa statistics and the rheumatologist’s findings considered the “gold standard”.Results: Data from 202 of the 203 enrolled patients were analyzed. There was fair-to-moderate agreement between PCPs and rheumatologists when assessing swelling of the small joints and wrist of the right side (range of kappa: 0.14–0.41) and low-to-moderate agreement in similar examinations of the left side (range of kappa: 0.04–0.42). Assessments of joint tenderness showed fair-to-moderate agreement for both the right side (range of kappa: 0.22–0.47) and left side (range of kappa: 0.24–0.45). P-values were significant for virtually all comparisons.Conclusion: MSK examinations by PCPs showed a promising extent of agreement in detecting IA with those by rheumatologists following training. Refinement of the standardized training process could further improve accuracy and help PCPs to confidently identify cases of early IA, thus allowing earlier intervention than is typical in this setting.Keywords: arthritis, physician training, primary care, referral criteria, rheumatic disease